PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE BENAR SALAH BERANTAI UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN TATA NAMA SENYAWA DAN PERSAMAAN REAKSI SEDERHANA DI KELAS X SMA NEGERI 11 PEKANBARU - Resta Andria Putri; Maria Erna; Abdullah Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: Research about application of active learning true false chain strategy has been done to know the improvement of student’s learning achievement at compounds nomenclature and chemical reaction equation subject in SMAN 11 Pekanbaru. This research was quasi experimental with pretest-posttest design. The sample consist of two classes, class X.10 as the experiment class and class X.9 as the control class that randomly selected after testing normality and homogeneity test. Active learning true false chain strategy applied in X.10. Data analysis technique used t-test. Results of data processing obtained tcount>ttable (2,81>1,67). It means the application of active learning true false chain strategy is able to improve the student’s learning achievement in the subject of compounds nomenclature and chemical reaction equation in SMAN 11 Pekanbaru. The result of normalized gain (N-gain) of experiment class is 0,75 as the high category.Key words: True false chain, Learning achievement, Compounds nomenclature and chemical reaction equationWisuda Oktober